Upaya Guru Menciptakan Lingkungan Yang Nyaman Melalui Manajemen Budaya Sekolah Yang Positif - Melyarmes Hodner Kuanine; Kristian Edison Yohanis Melkior Afi (Jurnal Manajemen Pendidikan Kristen, 2023)
Management of the learning process based on quality capacity is the responsibility and function of school leadership. The stages of planning, implementation, assessment and follow-up efforts must take precedence in the management process in schools. The management process must be carried out properly by qualified educators so that they can guide students to find their competence as a whole. This research was written with the aim of examining the issue of managing school culture which demands the attention of all stakeholders. Creating a comfortable learning environment is influenced by the quality standards of school culture management. The research method in this article is descriptive qualitative. The results of this study indicate that there is a positive correlation between the quality of the teacher workforce in terms of planning, evaluating, and using student learning outcomes. Good and careful management is a must for every learning leader as the main implementer which is effectively reflected in building consistency in the implementation of regular school culture management.